Analysis of Square-wave Bouts to Verify VO2max - Sedgeman, D.; Dalleck, L.; Clark, I. E.; Jamnick, N.; Pettitt, R. W. (International Journal of Sports Medicine, 2013)
Submaximal and supramaximal square-wave bouts have been reported to consistently verify ‘true’ VO2max. Although a direct comparison between both protocols exists, knowledge on the statistical consistency between the protocols using the same group of participants is lacking. The purpose of this study was to conduct an analysis of the submaximal and supramaximal verification bout performed shortly subsequent to a graded exercise test (GXT). On 2 separate occasions, 6 males and 7 females (age: 29±9 years) completed a GXT protocol and an exhaustive, square-wave bout at either end-GXT power minus 2-stages or 105% end-GXT power. No differences (p>0.05) in VO2max were observed between the GXT and square-wave bouts. The typical error (ml/kg/min) for submaximal (1.09) and supramaximal (1.04) trials was similar. Likewise, similar relative measures of consistency were observed for the submaximal (ICC α=0.97, CV=2.4%) and supramaximal trials (ICC α=0.95, CV=2.3%). For a GXT lasting ~10–12 min, the submaximal or supramaximal protocols appear to be equally effective.
Keywords: gas exchange threshold; graded exercise test; extreme domain; constant load exercise; VO2max; verification bout